Small bowel (jejunal) perforation as a suspected extrapulmonary manifestation of COVID-19 - Guzmán-Del-Giudice, Oscar Enrique (2020)
SARS-CoV-2 (Severe Acute Respiratory Syndrome-related Coronavirus 2) is a new discovered pathogen belonged to the beta-coronavirus family. Its disease was named COVID-19 (Coronavirus Disease 2019). It had been first reported on the city of Wuhan, Province of Hubei, Democratic Republic of China by the end of December of 2019, and it is the responsible of the current pandemic declared by WHO by March 2020.